Some consequences in weak processes of three-generation mixing in the leptonic sector - Peres, O. L.G. [UNESP]; Pleitez, V. [UNESP]; Zukanovich Funchal, R. (American Physical Society (APS), 1994)
We investigate the sensitivity of some weak processes to a Cabibbo-Kobayashi-Maskawa mixing in the leptonic sector. Values for mixing angles and masses compatible with several experimental accelerator data were found. We discuss in this context neutrino oscillations and cosmological and astrophysical consequences as well. © 1994 The American Physical Society.